Boys who rocked the world : heroes from King Tut to Bruce Lee - McCann, Michelle Roehm, 1968- (Aladdin ; Beyond Words, 2012)
Short profiles of famous men throughout history, from King Tut to Crazy Horse to Stan Lee to Shaun White.